PREVALENCE AND PATTERN OF TOBACCO USE IN RURAL AREA OF PESHAWAR - Shah, S. Humayun; Shah, S. Nasir; ullah, Rizwan (Journal of Ayub Medical College Abbottabad, 1993)
2975 cases were studied in two villages of Peshawar District. 48.44% were found tobacco users. Out of these 43.79% were males whereas females were only 4.4%. Nasswar was being the most frequently used (64.5%) type of tobacco followed by chillum (17.5%).